Alliance rupture and repair in early sessions of dialectical behavior therapy: The case of Rachel. Issue 2 (17th December 2020) - Boritz, Tali; Varma, Sonya; Macaulay, Christianne; McMain, Shelley F.
Abstract: Emotional and interpersonal instability are core features of borderline personality disorder (BPD) and can pose a challenge for the therapeutic relationship. In dialectical behavior therapy (DBT) for BPD, ruptures in the therapeutic alliance are considered through a behavioral lens that examines the client's relational learning history, the function and context of the rupture, as well as the patterns of emotional processing difficulties that underlie interpersonal conflict. In this article, we use the case of Rachel to illustrate how alliance‐focused approach can be integrated with DBT case formulation to enhance treatment planning and the successful negotiation of alliance ruptures.